Towards to a usable and accessible mixed global standard DTT-IPTV - Castro, C. (2016)
This proposal includes the establishment of a joint standard for the integration of interactive open platforms: GINGA for interactive service on ISDB-T and Hybrid European standard HbbTV with SiestaCloud ecosystem for IPTV together. In addition, this standard will be interoperable with close or half open Smart-TV standards like, AndroidTV, AppleTV, AmazonTV, etc.; the incompatibility that actually exists between these platforms will be solved by this project. Our proposal also includes development of interactive applications on DTT and IPTV which assumes usability (SIMPLIT) and accessibility (W3C) rules. The authoring tool implementation is also contemplated for the development of interactive applications, under the concept of open existing access repositories templates and an extension of Unity framework for interactive 3D content development without having to program a single code line. Finally, a production methodology of audiovisual content (i-standardized, accessible and usable) in cultural, health, educational and commercial context will also be proposed. © Springer International Publishing Switzerland 2016.